Higher Education Under Fire: Equity Policies in a Polarized World - Salmi, Jamil (International Higher Education, 2025)
<h3 id="universities-have-faced-an-exceptional-wave-of-backlash-against-the-promotion-of-equity-in-access-to-and-success-in-higher-education-in-recent-years-even-in-countries-with-a-long-democratic-tradition-this-article-analyzes-the-forms-and-consequences-of-this-backlash-and-outlines-the-type-of-research-needed-to-monitor-the-impact-of-measures-and-actions-to-continue-the-promotion-of-equity-and-inclusion-in-higher-education" data-pm-slice="1 1 []">Universities have faced an exceptional wave of backlash against the promotion of equity in access to and success in higher education in recent years, even in countries with a long democratic tradition. This article analyzes the forms and consequences of this backlash and outlines the type of research needed to monitor the impact of measures and actions to continue the promotion of equity and inclusion in higher education.